2013
DOI: 10.1021/co400005y
|View full text |Cite
|
Sign up to set email alerts
|

Uncatalyzed One-Pot Synthesis of Highly Substituted Pyridazines and Pyrazoline-Spirooxindoles via Domino SN/Condensation/Aza-ene Addition Cyclization Reaction Sequence

Abstract: A previously unknown class of highly substituted pyridazines and pyrazoline-spirooxinoles are easily prepared by an uncatalyzed one-pot three-component approach incorporating a domino SN/condensation/aza-ene addition cyclization reaction sequence. 1,1-Dihydrazino-2-nitroethylene (DHNE) which is generated in situ from the nucleophilic substitution (SN) reaction of hydrazine and 1,1-bis(methylthio)-2-nitroethylene (BMTNE), allowed to be condensed with active 1,2-dicarbonyl compounds followed by an intramolecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…1,1-Dihydrazino-2-nitroethylene 275, which was generated in situ from the nucleophilic substitution reaction of hydrazine 130 and 1,1-bis(methylthio)-2-nitroethylene 269, was isolated and allowed to condense with isatins 1 followed by an intramolecular aza-ene addition cyclization (Scheme 112). 206 A pseudo-fivecomponent reaction was also used in similar condition for the synthesis of the same products. This procedure avoided the isolation of the intermediate 275.…”
Section: Synthesis Involving Five-component Reactions Of Isatinsmentioning
confidence: 99%
“…1,1-Dihydrazino-2-nitroethylene 275, which was generated in situ from the nucleophilic substitution reaction of hydrazine 130 and 1,1-bis(methylthio)-2-nitroethylene 269, was isolated and allowed to condense with isatins 1 followed by an intramolecular aza-ene addition cyclization (Scheme 112). 206 A pseudo-fivecomponent reaction was also used in similar condition for the synthesis of the same products. This procedure avoided the isolation of the intermediate 275.…”
Section: Synthesis Involving Five-component Reactions Of Isatinsmentioning
confidence: 99%
“…In this reaction, multiple C-C or C-H bonds are formed in the same vessel, including different reaction mechanisms to form complex molecules without the purification of intermediates. These reactions are often used in medical or combinatorial chemistry to synthesize complex active drug molecules (Sudhapriya et al, 2014;Tietze et al, 2014;Fu et al, 2013;Shestopalov et al, 2013;Zohreh & Alizadeh, 2013;Renault et al, 2007). Domino reactions are classified as homo-domino processes and hetero-domino processes (Nesi et al, 1999).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Pyrazolines are very important five‐membered heterocyclic compounds, which are found as the central structure in a wide range of compounds that possess extensive bioactivities including antimicrobial, anticancer, anticonvulsant, antiviral, antitumor, anti‐inflammatory, and antifungal activities . Although some methods have been reported for the preparation of pyrazoline, most of these strategies suffer from various disadvantages such as low yields, low functional group tolerance, catalyst application, and tedious workup procedures. Recently, Alizadeh et al developed a novel synthesis of pyridazines and pyrazoline‐spirooxindoles by using 1,1‐dihydrazino‐2‐nitroethylene (DHNE) as a primary diamine.…”
Section: Introductionmentioning
confidence: 99%
“…Although some methods have been reported for the preparation of pyrazoline, most of these strategies suffer from various disadvantages such as low yields, low functional group tolerance, catalyst application, and tedious workup procedures. Recently, Alizadeh et al developed a novel synthesis of pyridazines and pyrazoline‐spirooxindoles by using 1,1‐dihydrazino‐2‐nitroethylene (DHNE) as a primary diamine. Based on our research, literature reviews revealed no other report on the application of DHNE.…”
Section: Introductionmentioning
confidence: 99%